Late-presenting congenital diaphragmatic hernia in an infant with tuberous sclerosis – case report and a review of the literature - Komarowska, Marta; Matuszczak, Ewa; Baran, Marcin; Dzienis-Koronkiewicz, Ewa; Hermanowicz, Adam; Dębek, Wojciech (Pediatria Polska - Polish Journal of Paediatrics, 2020)
Tuberous sclerosis complex (TSC) is a rare, genetic syndrome, which is characterized by the occurrence of small, benign multilocalised hamartomas. The clinical manifestation of the disease is variable, from mild to life threating. This report presents a 9-month-old male baby suffering from TSC, which was diagnosed prenatally. The child was under constant medical, multidisciplinary monitoring. This boy presented skin lesions, hamartomas in the brain and heart, and observation toward hamartoma of the right retina. The infant was admitted to the hospital because of vomiting, fever and cough. Chest X-ray showed left diaphragmatic hernia with mediastinum shift. He underwent thoracoscopic hernia repair. The postoperative period was complicated by a left pneumothorax, atelectasis and pneumonia, but finally the child recovered and remains under ambulatory monitoring. Every pathological symptom must be imaged and diagnosed, despite good general condition.